Preliminary Data on Species Composition and Distribution of Scolopendromorph Centipedes (Chilopoda: Scolopendromorpha) in Kon Ka Kinh National Park and Kon Chu Rang Nature Reserve (Gia Lai Province) - Xuan Son, Le; Thi Ha, Vu (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4, 2018)
Abstract: This s tudy investigates the species composition of Scolopendromorpha in Kon Ka Kinh National Park (NP) and Kon Chu Rang Nature Reserve (NR) (Gia Lai province) during the rainy season (May, June) and the dry season (November, December) in 2017 and 2018. Twelve species of 3 genera and 2 families were found. Among these species, Otostigmus striolatus, (Verhoeff, 1937), has been recorded for the first time for Vietnam and six other species, including Cryptops tahitianus, Otostigmus amballae, Otostigmus reservatus, Otostigmus astenus, Otostigmus reservatus, Scolopendra subspinipes, recorded for the first time for the studied area . The Scolopendridae Pocock (1895) was dominant with 11 species while Cryptopidae Kohlarausch (1881) had only one species reported. Most of the species were recorded in the primary forests and a few species were found in the pine forest. In addition, the number of species recorded in the rainy season was higher than that in the dry season; and the Cryptops Leach (1815) was found only in the rainy season. Keywords: Chilopoda, Scolopendromorpha, Kon Ka Kinh, Kon Chu Rang, centipedes. References [1] Thai Tran Bai, 2010, Invertebrate Zoology, Vietnam Education Publishing House. [2] Attems C., 1930, “Myriopoda. 2. Scolopendromorpha”, Das Tierreich, 54. [3] Hoang Xuan Vinh, 1998, Life of animal for medicine, Science and Technology Publishing House, Hanoi, 28-30. [4] Tran T.T.B., Le X.S., Nguyen D.A., 2013, “An annotated checklist of centipedes (Chilopoda) of Vietnam”, Zootaxa, 3722(2): 219-244. [5] Ghilarov M.S. (1975) "Dwelling conditions for animals of various dimentional groups in the soil". Methods of soil zoological studies. Nauka, Moscow: 7-11. [6] Górny M. & Grüm L. (1993) Methods in Soil Zoology. Elsevier Science. 460pp. [7] Attems C., 1953, “Myriopoden von Indochina. Expeditionvon Dr. Dawydoff. C, (1938-1939)”, Mémoires du Muséum National d’Histoire Naturelle, (Nouvelle Serie, Série A, Zoologie), 5(3): 133-230. [8] Schileyko A.A., 1992, “Scolopenders of Vietnam and some aspects of the system of Scolopendromorpha (Chilopoda: Epimorpha) (Part 1)”, Arthropoda Selecta, 1: 5-19. [9] Schileyko A.A., 1995, “The scolopendromorph centipedes of Vietnam (Chilopoda: Scolopendromorpha), (Part 2)”, Arthropoda Selecta, 4: 73-87. [10] Schileyko A.A., 2007, “The scolopendromorph centipedes (Chilopoda) of Vietnam, with contributions to the faunas of Cambodia and Laos (Part 3)”, Arthropoda Selecta, 16: 71-95. [11] Lewis G. E (2014). “A review of the orientalis group of the Otostigmus subgenus Otostigmus Porat, 1876 (Chilopoda: Scolopendromorpha: Scolopendridae)”. Zootaxa 3889 (3): 388–413 [12] Le Xuan Son, Nguyen Đuc Anh, Vu Thị Ha, Nguyen Đuc Hung, Tran Thi Thanh Binh, 2017, Diversity of Scolopendromorpha (Chilopoda: Scolopendromorpha) at Thach Nham, Kon Tum protection forest, Journal of Agriculture and Rural Development, 13/2017: 84-89.